Analisis Uji Kebocoran Pesawat Sinar-X: X-Ray Leakage Test Analysis - Syahrani, Edelweisa Aulia (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
One of the aspects in ensuring the safe operation of x-ray machines in the field of industrial radiography is safety verification. The safety verification of x-ray machines for industrial radiography can be performed through leakage testing. In this study, the leakage test of the x-ray machine was conducted using the direct dose measurement method in four different directions. From the calculation results, each dose rate in the lower, left, upper, and right directions are 0,124 mSv/hour; 0,326 mSv/hour; 0,0326 mSv/hour; and 0,627 mSv/hour. Thus, the x-ray machine used in this study was identified as reliable and not experiencing leakage because the dose rate values in all directions were less than 10 mSv/hour.